PENGAJARAN CARA MENGISI DATA AWAL PERUSAHAAN DAGANG DALAM MYOB DI SMK DEWI SARTIKA JAKARTA - Vennessa; Chelsya (Jurnal Serina Abdimas, 2024)
Teaching at Dewi Sartika Vocational School is a teaching assistance program in the Merdeka Belajar Kampus Merdeka curriculum at Tarumanagara University with the aim of facilitating journaling for Dewi Sartika Vocational School students in various exercises on MYOB subjects. The duration of teaching assistance activities is from 1 August 2023 – 30 November 2023. Delivery of MYOB material is carried out in class and in the Computer Lab. Some of the benefits that can be felt when participating in this activity are training yourself to appear more confident when speaking in front of many people, being able to understand and get to know the different characters of each individual, and can train your social spirit. The result of this teaching for students is to gain knowledge about how and the process of filling in initial trading company data in MYOB. These results can be seen from how students are no longer confused in filling in initial trading company data in MYOB.